Influence of supply and demand factors on the development of environmentally responsible housing and utilities sector in the Russian Federation - Budakov, Alexey; Safronova, Natalia; Urubkov, Alexey; Myltsev, Mikhail (Serbian Journal of Management, 2016)
Empirical marketing regional research on supply and demand factors of housing and communal services (HCS) revealed determinants of customer loyalty and satisfaction with the service level and factors influencing on willingness to purchase additional services. Specific features of housing and utilities sector (HUS) as a social significant industry determine requirements to models reflecting reciprocal influence of indices of satisfaction, loyalty and economic indices of operation. The article presents definition of requirements along with development of techniques for modeling influence of satisfaction and loyalty on consumer behaviour of clients. The authors demonstrate trustworthy statistical results of correlative interrelationship of different factors. There have been designed regression models for taking management solutions by executives of management company housing and communal services at the development environmental responsibility. The causes that lead and hamper development of socially oriented services in different regions of the Russian Federation have been identified.